2016
DOI: 10.1177/0269216316651570
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Meaning-Centered Psychotherapy for the palliative care setting: Results of a pilot study

Abstract: Aims To establish preliminary evidence for the feasibility, acceptability, and utility of an abbreviated version of Meaning-Centered Psychotherapy tailored to the needs of palliative care patients in the final weeks or months of life. Background Surprisingly, few mental health interventions have specifically targeted the psychological needs of palliative care patients, when physical comfort seems to take precedence over mental health and emotional needs. Yet the need for mental health services targeting thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 32 publications
(41 reference statements)
2
70
0
6
Order By: Relevance
“…Therefore, the goal is to understand whether they are suffering (as it is one of the necessary conditions of MAiD), and to alleviate it where possible. Alleviation of suffering may take the form of symptom management or interventions such as dignity therapy 5 or meaning-centred therapy, 6 which may be helpful in treating emotional or existential suffering associated with end of life. Dignity therapy involves reflecting on a person's life experience, learning and achievements; and facilitates expression of their hopes for their loved ones in a legacy document.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the goal is to understand whether they are suffering (as it is one of the necessary conditions of MAiD), and to alleviate it where possible. Alleviation of suffering may take the form of symptom management or interventions such as dignity therapy 5 or meaning-centred therapy, 6 which may be helpful in treating emotional or existential suffering associated with end of life. Dignity therapy involves reflecting on a person's life experience, learning and achievements; and facilitates expression of their hopes for their loved ones in a legacy document.…”
Section: Discussionmentioning
confidence: 99%
“…5 Meaningcentred therapy attempts to develop a sense of meaning or purpose in a person's life, adapted to a palliative care setting. 6 Notably, as outlined in Bill C-14, there is no requirement that patients exhaust all options for symptom control before accessing MAiD (Box 1). 7 Although patients must be adequately informed of all available options for symptom control, a patient's rejection of any or all options that they find unacceptable does not preclude them from accessing MAiD.…”
Section: Discussionmentioning
confidence: 99%
“…MCGP was adapted for cancer survivors (MCGP-CS) by Van der Spek et al 8 There is evidence that MCGP and MCGP-CS are effective in enhancing a sense of meaning, psychological well-being, and reducing depressive symptoms. 5,[8][9][10] MCGP-CS is likely to be cost-effective as well. 11 In a randomized controlled trial (RCT) among advanced cancer patients, MCGP was more effective than supportive group psychotherapy (SGP) in improving quality of life, spiritual well-being, and reducing depression and hopelessness.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements were sustained during the 2-month follow-up period. 5 Van der Spek et al 9 Several other types of existential interventions have been developed, [12][13][14][15][16] and a few studies reported on the long-term effects of these interventions. In four RCT's on experiential-existential, 17 cognitiveexistential, 13 or supportive expressive group psychotherapy, 18 participants improved over the 1-year follow-up period, but not more than after a non-meaning-focused type of group psychotherapy 16,17 or the care as usual condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation